PDK1/mTOR Signaling in Myeloid Cells Differentially Regulates the Early and Late Stages of Sepsis - Juan Du; Guoli Li; Mingxi Hua; Junyan Han; Yu Hao; Hui Zeng; Ang Li; Yaxian Kong (Mediators of Inflammation)
The cecal ligation and perforation (CLP) model is the gold standard for the polymicrobial sepsis. In the CLP mice, the myeloid cells play an important role in septic shock. The phenotypes and the activation state of the macrophage and neutrophil correlate with their metabolism. In the present study, we generated the specific myeloid deletion of PDK1 and mTOR mice, which was the important regulator of metabolic signaling. We found that the deletion of PDK1 in the myeloid cells could aggravate the early septic shock in the CLP mice, as well as the deletion of mTORC1 and mTORC2. Moreover, PDK1 deletion attenuated the inflammation induced by LPS in the late stage on CLP mice, which was exacerbated in mTORC1 and mTORC2 knockout mice. Both PDK1 and mTORC1/2 could not only regulate the cellular metabolism but also play important roles on the myeloid cells in the secondary stimulation of sepsis. The present study will provide a theoretical prospect for the therapy of the septic shock in different stages.